2008
DOI: 10.1586/14779072.6.8.1115
|View full text |Cite
|
Sign up to set email alerts
|

Circulating endothelial progenitor cells in cardiovascular disorders

Abstract: The role of vascular endothelium in cardiovascular disorders is well recognized. Mature endothelial cells contribute to the repair of endothelial injury, but only with a limited capacity. This has led to growing interest and further investigation into circulating endothelial progenitor cells (EPCs) and their role in vascular healing, repair and postnatal neovascularization. Recent studies have shown that EPCs are affected both in number and function by several cardiovascular risk factors as well as various car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
2
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 62 publications
0
14
2
1
Order By: Relevance
“…In the present study, the lack of association between an increase in the number of CECs and MACEs or ISR observed in stable CAD patients could be related to different underlying pathogenic processes triggering endothelial detachment. [28,29]. In contrast to previous studies, we showed that BMS implantation induces early mobilization of CD34 + PCs and CD34 + KDR + EPCs.…”
Section: Relationship Between Endothelial Markers and Macescontrasting
confidence: 99%
“…In the present study, the lack of association between an increase in the number of CECs and MACEs or ISR observed in stable CAD patients could be related to different underlying pathogenic processes triggering endothelial detachment. [28,29]. In contrast to previous studies, we showed that BMS implantation induces early mobilization of CD34 + PCs and CD34 + KDR + EPCs.…”
Section: Relationship Between Endothelial Markers and Macescontrasting
confidence: 99%
“…This recent registry from Germany found the greatest improvement occurred in patients with PPCM receiving bromocriptine on top of standard therapy. 9 However, the percent of patients showing full recovery of LV function was similar in the 2 groups, in addition, patients with low LVEF failed to improve, suggesting that treatment with bromocriptine was not effective in sicker patients with PPCM. Therefore, it is still a matter of significant debate over the role of bromocriptine as a part of standard management of PPCM, and large-scaled controlled study has to be done to establish the efficacy of bromocriptine.…”
Section: Angiogenic Imbalance In Post-ppcm Women With LV Recoverymentioning
confidence: 86%
“…5,6 Recently, the 2-hit hypothesis was proposed: one hit is the late-gestational hormonal changes with vasotoxic effects, including sFlt1 and prolactin, and the second hit is a predisposed inability to resist this insult in some women, probably because of some baseline altered endothelial function. 7,8 In addition, a progressive increase in the number of circulating endothelial progenitor cells (EPCs) during pregnancy in healthy women has been found in most studies, 9,10 but no data exist on women with PPCM.…”
mentioning
confidence: 99%
“…2). Существуют исследования, в которых нарушение мобилизации и истощение ЭПК рассматривается как маркер эндотелиальной дисфункции и фактор риска прогрессирования сердечно-сосудистых за-болеваний [37,39,40,41,57] и прогрессирования субклинического атеросклероза [38,41], их также можно рассматривать как предиктор повторных сердечно-сосудистых событий у пациентов с уже перенесенным атеротромботическим инсультом или инфарктом миокарда [42]. В проапоптотиче-ской среде также может отмечаться увеличение микрочастиц, происходящих из ЭПК, что снижа-ет уровень циркулирующих ЭПК и таким образом способствует повышению жесткости аорты и ри-ска сердечно-сосудистых событий [43,56].…”
Section: эндотелиальные прогениторные клетки (эпк)unclassified